2016
DOI: 10.1292/jvms.15-0412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intrauterine infusion of povidone-iodine on endometrial cytology and bacteriology in dairy cows with clinical endometritis

Abstract: Endometritis is one of the major diseases causing infertility in the cow. Intrauterine infusion of povidone-iodine (PVP-I) is a common treatment. However, the optimal concentration of PVP-I for treating endometritis effectively remains unknown. We tested concentrations of 2.0% or 0.5% PVP-I for treating clinical endometritis in dairy cattle. In Experiment 1, bacteria isolated from the uterus were incubated with either 2.0% or 0.5% PVP-I, and the numbers of bacterial colonies were counted. In Experiment 2, 18 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
(38 reference statements)
1
21
1
1
Order By: Relevance
“…This is because >5% PMNs generally indicates impaired reproductive performance [ 1 ]. In addition, a decrease in bacterial infection and the percentage of PMNs is reflected in a reduction of the VDS [ 13 ]. Although cytology is a very useful method for diagnosing endometritis, this method is less suitable for clinical practice because it is more costly and time consuming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because >5% PMNs generally indicates impaired reproductive performance [ 1 ]. In addition, a decrease in bacterial infection and the percentage of PMNs is reflected in a reduction of the VDS [ 13 ]. Although cytology is a very useful method for diagnosing endometritis, this method is less suitable for clinical practice because it is more costly and time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of clinical endometritis in dairy cows 15 to 60 days postpartum ranges from 23.6 to 42.6% [ 3 , 4 , 10 , 16 ]. Although different treatment methods have been utilized for endometritis, valid diagnostic criteria and optimal treatment timing have not been elucidated [ 2 , 7 , 8 , 12 , 13 , 22 , 23 ]. Rectal palpation of the genital tract is the most commonly used clinical method to detect uterine abnormalities due to its simplicity and rapid implementation in the field of veterinary practice [ 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various therapies in cows with endometritis have been carried out using antibiotics, prostaglandins [5,6,7], and Lugol [8,9,10]. The use of Lugol 1% can treat reproductive disorders of cattle like uterus infection [11].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate changes in the degree of endometrial inflammation, PMN% was measured every 24 hr for 8 days. A previous study showed that intrauterine infusion of PVP-I decreased PMN% within two weeks in cows with endometritis [ 18 ]. In the present study, the PVP group had transient inflammation the day after infusion that was reduced after 48 hr.…”
Section: Discussionmentioning
confidence: 99%